PENGARUH KELEMBABAN TANAH TERHADAP KARAKTER AGRONOMI, HASIL RAJANGAN KERING DAN KADAR NIKOTIN TEMBAKAU (Nicotiana tabacum L; Solanaceae) TEMANGGUNG PADA TIGA JENIS TANAH [Soil Moisture Effects on Agronomic Characters, Yield and Nicotine Content of Temanggung Tobacco (Nicotiana tabacum L; Solanaceae) at Three Types of Soil] - Djumali, Djumali; Mulyaningsih, Sri (Research Center for Biology-Indonesian Institute of Sciences, 2014)
Research on the effect of soil moisture on agronomic characters, yield and nicotine content of Temanggung tobacco has been conducted in the Research Institute for Tobacco and Fibre Crops at Malang, East Java from March to October 2010. The treatment has been arranged in a Splitplot design with 3 replications. The experimental plot consisted of three types of soil: Complex Eutrudepts-Hapludalfs, Vitraquands, and Complex Dystrudepts-Hapludalfs. The subplot comprised 5 levels of soil moisturation: 60, 70, 80, 90, and 100% of field capacities. The results showed that the dry slice yield, content of nicotine, and agronomic characters of the Temanggung tobacco were affected by the result of interaction between soil moisture and type. The decreasing of soil moisture up to 40% from field capacity in the Complex Eutrudepts- Hapludalfs had decreased dry slice yield, nicotine content, plant height, root length, dry weight of plant, shoots, roots, stems, leaves, flowers, and suckers accounted for 54.3, 19.3, 33.7, 17.1, 74.1, 71.4, 82.3, 80.1, 54.3, 60.5 and 86.5% respectively, in the Vitraquands 72.7,20.2, 37.0, 13.2, 79.8, 78.5, 84.3, 80.7, 72.7, 63.3 and 87.8% respectively, and in the Complex Dystrudepts-Hapludalfs 74.2, 23.0, 39.6, 15.7, 79.3, 78.0, 83.6, 80.3, 74.2, 79.1 and 80.6% respectively.